2017
DOI: 10.1182/blood-2016-07-730648
|View full text |Cite
|
Sign up to set email alerts
|

A randomized assessment of adding the kinase inhibitor lestaurtinib to first-line chemotherapy for FLT3-mutated AML

Abstract: The clinical benefit of adding FMS-like tyrosine kinase-3 (FLT3)-directed small molecule therapy to standard first-line treatment of acute myeloid leukemia (AML) has not yet been established. As part of the UK AML15 and AML17 trials, patients with previously untreated AML and confirmed FLT3-activating mutations, mostly younger than 60 years, were randomly assigned either to receive oral lestaurtinib (CEP701) or not after each of 4 cycles of induction and consolidation chemotherapy. Lestaurtinib was commenced 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
132
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(133 citation statements)
references
References 28 publications
(34 reference statements)
1
132
0
Order By: Relevance
“…Because the quantitative relationship between FLT3 activity and clinical outcome (i.e., overall survival and objective response rate) has been establised,8, 17, 18 it is appropriate to utlilize the degree of target inhibition from early clinical trials as a surrogate marker to support dosing selection. Sorafenib and its N‐oxide metabolite showed a concentration‐dependent inhibitory effect on both FLT3 and ERK activities 9.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the quantitative relationship between FLT3 activity and clinical outcome (i.e., overall survival and objective response rate) has been establised,8, 17, 18 it is appropriate to utlilize the degree of target inhibition from early clinical trials as a surrogate marker to support dosing selection. Sorafenib and its N‐oxide metabolite showed a concentration‐dependent inhibitory effect on both FLT3 and ERK activities 9.…”
Section: Discussionmentioning
confidence: 99%
“…FLT3 activating mutations are commonly present as internal tandem duplication (ITD) mutations (FLT3‐ITD) or point mutations in the second tyrosine kinase domain (FLT3‐TKD) in ∼25–30% or 5–10% of patients, respectively 5, 7. Currently, several FLT3 inhibitors are being investigated in patients with AML 8, 9. In 2017, the US Food and Drug Administration (FDA) approved the pan‐kinase/FLT3 inhibitor, midostaurin in patients with FLT3‐ITD and TKD‐positive AML based on prolongation of both event‐free and overall survival in the subgroup receiving midostaurin in combination with standard induction chemotherapy 10…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Within this trial, newly diagnosed AML patients with activating FLT3 mutations (median age, 49 years; range 5-68 years) were randomised to receive either oral lestaurtinib or placebo, for up to 28 days after each of the four courses of chemotherapy. 95 Recently published data showed that lestaurtinib yielded no improvements in 5-year RFS and OS when added to first-line chemotherapy. 95 Nevertheless, subgroup analysis indicated improved OS and significantly reduced rates of relapse in lestaurtinib-treated patients who sustained >85% FLT3 inhibition as assessed by the plasma inhibitory activity assay.…”
Section: Results Of Clinical Trials With Tyrosine Kinase Inhibitor Trmentioning
confidence: 99%
“…95 Recently published data showed that lestaurtinib yielded no improvements in 5-year RFS and OS when added to first-line chemotherapy. 95 Nevertheless, subgroup analysis indicated improved OS and significantly reduced rates of relapse in lestaurtinib-treated patients who sustained >85% FLT3 inhibition as assessed by the plasma inhibitory activity assay. 95 In addition, elevated FLT3 ligand had no impact on lestaurtinib plus chemotherapy treatment.…”
Section: Results Of Clinical Trials With Tyrosine Kinase Inhibitor Trmentioning
confidence: 99%